2017
DOI: 10.1148/radiol.2017161687
|View full text |Cite
|
Sign up to set email alerts
|

Luminal Water Imaging: A New MR Imaging T2 Mapping Technique for Prostate Cancer Diagnosis

Abstract: Purpose-To assess the feasibility of luminal water imaging (LWI), a quantitative T 2 -based MRI technique, for the detection and grading of prostatic cancer (PCa).Material and Methods-18 patients with biopsy proven PCa provided informed consent to be included in this institutional human ethics board approved prospective study between January 2015, and January 2016. Patients underwent 3T MRI shortly before radical prostatectomy. T 2 distributions were generated with regularized Non-Negative Least Squares (NNLS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 24 publications
3
96
1
Order By: Relevance
“…Our estimates of short and long T 2 components and LWF were consistent with previous reports using NNLS fitting, indicating that our approach can be considered as a fully model‐based equivalent to the NNLS technique. BIC revealed a moderate preference for monoexponential fitting in tumor and the identification of regions of monoexponential decay may be useful for tissue characterization . Another advantage of estimation via mono‐ and biexponential models over NNLS methods is that they can be combined with a Rician noise model to explicitly account for the noise floor signal in voxels with low signal‐to‐noise ratio (SNR) at long echo times.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our estimates of short and long T 2 components and LWF were consistent with previous reports using NNLS fitting, indicating that our approach can be considered as a fully model‐based equivalent to the NNLS technique. BIC revealed a moderate preference for monoexponential fitting in tumor and the identification of regions of monoexponential decay may be useful for tissue characterization . Another advantage of estimation via mono‐ and biexponential models over NNLS methods is that they can be combined with a Rician noise model to explicitly account for the noise floor signal in voxels with low signal‐to‐noise ratio (SNR) at long echo times.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the proportions of the short and long T 2 components are likely to vary with histological tumor grade. This is supported by findings showing that the fractional amount of the long T 2 component, termed the luminal water fraction (LWF), is also correlated with the amount of luminal space and is negatively correlated with increasing Gleason grade . There is also emerging evidence that ADC is associated with the amount of luminal space …”
mentioning
confidence: 77%
See 1 more Smart Citation
“…This would allow for a reduced number of protocols for grading prostate cancer, reducing overall scan times. The AUC for the detection of PCa is also lower in this study than previous results, possibly due to previous studies using patients scheduled for retropubic prostatectomy, weighting the lesions towards more advanced tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Sabouri et al implemented a method to investigate quantitative T 2 imaging in the prostate, proposing the LWI technique, which produces an estimate of the fractional volume of luminal water in each voxel of the prostate, the luminal water fraction (LWF). Sabouri et al have shown that there is a good correlation between LWF and histologically measured luminal fractional volume and determined that LWI shows promise in being able to detect PCa and predict Gleason score . However, the fitting method used has a high number of degrees of freedom, potentially making it vulnerable to noise and local minima.…”
mentioning
confidence: 99%